MODERNITAS NUSYUZ; ANTARA POLA PENGAJARAN SUAMI TERHADAP ISTRI ATAU KDRT - Azzulfa, Fatihatul Anhar (Institut Agama Islam Negeri (IAIN) Syekh Nurjati Cirebon, 2025)
AbstractCreating a happy and eternal family is a basic concept in building a household. Realizing it is not an easy matter, disharmony between husband-and-wife relations is one of the underlying factors. The attitude of disobedience or neglect of obligations shown by the wife is the cause of the estrangement of relationships in household life, or nusyuz. This phenomenon is still the prima donna in Islamic studies. This article is included in library research using a qualitative study with a descriptive-analytical nature. The results of the study show that the nusyuz conception needs to be reinterpreted according to socio-cultural factors. The act of beating a husband against his wife, which is indicated by nusyuz, should be interpreted as a pattern of educating (educating) the wife, but it can turn into domestic violence if the act of 'beating' indicates physical violence, psychological or emotional violence, sexual violence, or neglect of the household.Keywords: Nusyuz, Husband Education for Wife, Domestic ViolenceAbstrak Mewujudkan keluarga yang bahagia dan kekal merupakan konsep dasar dalam membangun rumah tangga. Merealisasikannya bukan perkara mudah, disharmoni antara relasi suami istri menjadi salah satu faktor yang mendasari. Sikap tidak patuh atau pengabaian kewajiban yang ditunjukkan oleh istri menjadi penyebab renggangnya hubungan dalam kehidupan rumah tangga atau dinamakan nusyuz. Fenomena ini masih menjadi primadona dalam kajian keislaman. Artikel ini termasuk dalam penelitian kepustakaan (library research) menggunakan kajian kualitatif dengan bersifat deskriptif analisis. Hasil penelitian menunjukkan bahwa konsepsi nusyuz perlu reinterpretasi ulang sesuai sosio-kultural. Tindakan pemukulan suami terhadap istri yang diindikasi nusyuz hendaknya dimaknai sebagai pola pengajaran (mendidik) istri, tetapi dapat beralih menjadi KDRT jika tindakan ‘pemukulan’ tersebut terindikasi adanya kekerasan fisik, kekerasan psikis/emosional, kekerasan seksual dan penelantaran rumah tangga. Kata kunci: Nusyuz, Pengajaran Suami Tehadap Istri, KDRT